2022
DOI: 10.21926/obm.geriatr.2204214
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Comorbidities and Cognitive Impairment

Abstract: Various grades of cognitive impairment generally occur in older adults over the age of 55, where cardiovascular risk factors such as diabetes and/or hypertension, coronary artery disease, or cerebrovascular accidents are also common. Cognitive impairment occurs in various forms, from mild or amnesia such as forgetting today's date to more ominous and progressive forms, such as frank dementia. Over 5 million people worldwide suffer from dementia, most of whom live in low- and middle-income countries. It has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In a similar vein, by conducting a secondary prevention study with 200 men aged 57.3±6.3 years, the work of Lutski et al [ 34 ] showed that subjects with two or more chronic conditions had a greater probability of experiencing subjective cognitive impairment over a 20-year follow-up period. Taken together, it appears that comorbidities result in physical and functional limitations or changes in brain macrostructure and microstructure, which have a negative impact on cognitive function [ 35 , 36 ] or vice versa [ 37 , 38 ]. As a result, a prospective cohort study will be required to determine the precise direction of the relationship between comorbidities and cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar vein, by conducting a secondary prevention study with 200 men aged 57.3±6.3 years, the work of Lutski et al [ 34 ] showed that subjects with two or more chronic conditions had a greater probability of experiencing subjective cognitive impairment over a 20-year follow-up period. Taken together, it appears that comorbidities result in physical and functional limitations or changes in brain macrostructure and microstructure, which have a negative impact on cognitive function [ 35 , 36 ] or vice versa [ 37 , 38 ]. As a result, a prospective cohort study will be required to determine the precise direction of the relationship between comorbidities and cognitive function.…”
Section: Discussionmentioning
confidence: 99%